The Evaluation of Health Promotion Media Availability in Elementary Schools - Wiwik Eko Pertiwi; Annissa Annissa (Jurnal Promkes: The Indonesian Journal of Health Promotion and Health Education, 2019)
Background: Health promotion is an effort to distribute health messages to all levels of society. In order for the achievement of the main purpose of health promotion , media or tools are needed so  health promotion becomes effective and efficient. The lack of availability of health promotion media especially in elementary schools is still low, so that it affects the low condition of student knowledge and attitudes in healthy behaviors. Purpose: This study was aimed to determine the availability of health promotion media in elementary schools (SD) in Kramatwatu District, Serang Regency, Banten Province. Methods: This study was conducted on December 2017 to July 2018 with a total sample of 31 elementary schools. The study uses a descriptive design that is described in depth about the availability of health promotion media in elementary schools. Results: The results showed that out of 31 elementary schools located in Kramatwatu sub-district, it was found that 64.5% of elementary schools had health promotion media, 29.0% of elementary schools stated that the type of health promotion media were posters, 19.4% were available as health promotional media in book form. A total of 38.7% stated that the number of health promotion media was lacking, 25.8% of the number of health promotion media was sufficient. The health promotion media that are most often accessed by elementary school students were books (67.7%). Conclusion: the availability of health promotion media in elementary schools of Kramatwatu District is still categorized as low.